Climatology of discomfort index and air quality index in a large urban mediterranean agglomeration - Poupkou, A.; Nastos, P.; Melas, D.; Zerefos, C. (Water, Air, and Soil Pollution, 2011)
The paper studies the climatology of the Discomfort Index (DI) and the Common Air Quality Index (CAQI) in a large Mediterranean urban center (Greater Thessaloniki Area), examines the relations between the indices and the climatic conditions in the study area and investigates the linkage between the Urban Heat Island (UHI) effect and the enhanced discomfort and poor air quality in the city center. Discomfort conditions are more enhanced during July and August. Atmospheric conditions when the population suffers discomfort and feels severe stress are found mainly in the summer season hours with total frequency that can be up to about 4% in a month. Throughout the year, air quality conditions are unhealthier in the stations of urban characterization. Very high daily CAQI values are more frequent during the cold period (about 14%) than during the warm period (1-2%) of the year in the urban stations. Daily DI∈≥24°C could be more associated to increased temperature than relative humidity and is strongly related to high and very high CAQI values. During summer, when daily CAQI is ≥76, the feeling of discomfort is the most probable. Consequently, a strong synergy between discomfort and bad air quality exists in summertime. High and very high CAQI values and the discomfort feeling by the majority of the population are related to stagnant atmospheric conditions. During summer season, the poor air quality and the unfavorable comfort conditions for the majority of the population in the city center are associated with the greater frequency of a more intense UHI effect. The above phenomenon is more pronounced during nighttime than daytime. © 2011 Springer Science+Business Media B.V.
Keywords: Agglomeration; Air pollution; Air quality; Air quality index; air temperature; article; Atmospheric conditions; Atmospheric humidity; Central Macedonia; circadian rhythm; Climate; climate conditions; Climatic conditions; Climatology; cold climate; Comfort conditions; Common Air Quality Index; Discomfort index; environmental impact assessment; Greater Thessaloniki Area; Greece; heat; heat island; humidity; Increased temperature; mass; Quality assurance; Quality indices; Relative humidity; seasonal variation; stress; Study areas; summer; Summer season; temperature; Thessaloniki; Thessaloniki [Central Macedonia]; Thessaloniki [Thessaloniki (DPR)]; urban area; Urban centers; Urban heat island; urban population; Urban stations